2014
DOI: 10.3892/mco.2014.367
|View full text |Cite
|
Sign up to set email alerts
|

Pre-chemotherapy preservation of fertility in male patients with high-grade malignant bone and soft tissue tumors

Abstract: Abstract. Only a limited number of orthopedic oncologists make arrangements for pre-chemotherapy fertility preservation, such as sperm cryopreservation, for their patients. The purpose of this study was to offer fertility preservation to male patients with high-grade malignant bone and soft tissue tumors and assess the outcomes. The study included 14 male patients, aged <45 years, with high-grade bone and soft tissue tumors. The median age at diagnosis was 23.0±12.0 years (range, 8-42 years). Following patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Reasons for exclusion are depicted in Figure . A total of 42 studies could be included in this review (Achille et al, ; Armuand et al, ; Babb et al, ; Bann et al, ; Boltezar et al, ; Branvall et al, ; Brydøy et al, ; Chang, Chen, Chen, & Hsieh, ; Crha et al, ; Fitoussi et al, ; Gilfillan et al, ; Girasole et al, ; Greaves et al, ; Grover, Deal, Wood, & Mersereau, ; Harrison, Welch, Matook, & Schwartz, ; Hoshi et al, ; van der Kaaij et al, ; Kamimura, Matsumoto, Zhou, Moriyama, & Saijo, ; Kelvin et al, ; Klosky, Anderson, et al, ; Klosky, Flynn, et al, ; Klosky et al, ; Klosky, Wang, et al, ; Kumar, Merali, Pond, & Zbuk, ; Latif & Ali, ; Naccache et al, ; Neal et al, ; Noetzli et al, ; Pacey et al, ; Ping, Gu, Li, Huang, & Li, ; Ramstein et al, ; Richter, Mehnert, & Geue, ; Rieker, Fitzgerald, & Kalish, ; Rooney et al, ; Rotker et al, ; Schover et al, ; Schover, Rybicki, Martin, & Bringelsen, ; Sheth et al, ; Shnorhavorian et al, ; Sonnenburg, Brames, Case‐Eads, & Einhorn, ; Wang, Chen, Ruan, & Cheung, ; Xu et al, ). No additional study could be identified by checking the references of included papers, and we did not receive any additional relevant studies by contacting the corresponding authors of included trials.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Reasons for exclusion are depicted in Figure . A total of 42 studies could be included in this review (Achille et al, ; Armuand et al, ; Babb et al, ; Bann et al, ; Boltezar et al, ; Branvall et al, ; Brydøy et al, ; Chang, Chen, Chen, & Hsieh, ; Crha et al, ; Fitoussi et al, ; Gilfillan et al, ; Girasole et al, ; Greaves et al, ; Grover, Deal, Wood, & Mersereau, ; Harrison, Welch, Matook, & Schwartz, ; Hoshi et al, ; van der Kaaij et al, ; Kamimura, Matsumoto, Zhou, Moriyama, & Saijo, ; Kelvin et al, ; Klosky, Anderson, et al, ; Klosky, Flynn, et al, ; Klosky et al, ; Klosky, Wang, et al, ; Kumar, Merali, Pond, & Zbuk, ; Latif & Ali, ; Naccache et al, ; Neal et al, ; Noetzli et al, ; Pacey et al, ; Ping, Gu, Li, Huang, & Li, ; Ramstein et al, ; Richter, Mehnert, & Geue, ; Rieker, Fitzgerald, & Kalish, ; Rooney et al, ; Rotker et al, ; Schover et al, ; Schover, Rybicki, Martin, & Bringelsen, ; Sheth et al, ; Shnorhavorian et al, ; Sonnenburg, Brames, Case‐Eads, & Einhorn, ; Wang, Chen, Ruan, & Cheung, ; Xu et al, ). No additional study could be identified by checking the references of included papers, and we did not receive any additional relevant studies by contacting the corresponding authors of included trials.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies followed a retrospective approach (38/42). Only four trials were executed prospectively: Hoshi et al () (Japan): 11 patients; Klosky, Flynn, et al () (USA and Canada): 146 patients; Klosky, Wang, et al () (USA and Canada): 99 patients; and Klosky, Flynn, et al () (USA and Canada): 122 patients. Three studies comprise more than one cohort (Kelvin et al, ; Klosky, Wang, et al, ; Rotker et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations